Comparative effects of two calcaneal lengthening osteotomies (Hintermann vs. Evans) in stage II adult-acquired flatfoot - Cheng Hao; Zi Li; Chenyu Xu; Yaping Ye; Jingjing Zhao; Wei Xie; Zhenhua Fang (BMC Musculoskeletal Disorders)
Abstract Background Stage II adult-acquired flatfoot (AAF) could be effectively treated by Hintermann (H) and Evans (E) lateral column lengthening (LCL) calcaneal osteotomies. This retrospective cohort study was aimed to compare the post-surgical outcome of this two osteotomies used in Chinese patients. Methods Of 114 eligible patients (149 feet) with Stage II AAF admitted from October 2018 to October 2022, 92 feet treated by Hintermann osteotomy and 57 feet treated by Evans osteotomy were observed in 2-year follow-up. Pre-surgical and post-surgical radiographic parameters, clinic scores and degenerative changes of related joints were collected and analyzed. Result Pitch angle, Meary’s angle, Naviculocuboidal (NC) overlap (%), Medial arch sagittal (MAS) angle, Talocalcaneal (TC) angle, Talonavicular (TN) coverage angle, Talus–second metatarsal (T-2MT) angle were significantly corrected by both H-LCL and E-LCL osteotomies (P <.05). The clinic scores of AOFAS (American Orthopaedic Foot & Ankle Society) score, SF-36 (Short-Form 36-item Health Survey), Pain-NRS (Numerical Rating Scale), and UCLA (University of California at Los Angeles activity score) after surgery showed significant improvement for the patient in both groups. Comparing between the two groups, no significant differences were found regarding to radiographic parameters, clinic scores or degenerative changes. However, degenerative changes of calcaneocuboidal (CC) joint were found in 6 cases (6.5%) in H-LCL group and 17 cases (29.8%) in E-LCL group. Degenerative changes of subtalar joint were found in 6 cases (6.5%) in H-LCL group and 17 cases (24.6%) in E-LCL group. One case developed complication of osteotomy nonunion, and one case underwent secondary arthrodesis in E-LCL group. Conclusion Both H-LCL and E-LCL osteotomies give rise to an outstanding radiographic correction and a significant enhancement of clinic scores in flatfoot deformity. Compared to E-LCL, H-LCL tends to protect the subtalar joint for Chinese patients.